Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Evaluate the infinite series:
[tex]\[ \sum_{n=1}^{\infty} \frac{9^n}{n(-2)^{n+1}} \][/tex]


Sagot :

Certainly! Let's evaluate the infinite series:

[tex]\[ \sum_{n=1}^{\infty} \frac{9^n}{n (-2)^{n+1}}. \][/tex]

1. Identify the General Term:
Let's denote the general term of the series by [tex]\( a_n \)[/tex]:
[tex]\[ a_n = \frac{9^n}{n (-2)^{n+1}}. \][/tex]

2. Simplify the General Term:
We notice that [tex]\( (-2)^{n+1} = (-2) \cdot (-2)^n \)[/tex]:
[tex]\[ a_n = \frac{9^n}{n \cdot (-2) \cdot (-2)^n} = \frac{9^n}{-2 \cdot n \cdot (-2)^n}. \][/tex]

3. Combine the Powers in the Denominator:
Combine [tex]\( (-2) \cdot (-2)^n \)[/tex]:
[tex]\[ (-2) \cdot (-2)^n = (-1)^{n+1} \cdot 2^n. \][/tex]
Therefore,
[tex]\[ a_n = \frac{9^n}{n \cdot (-1)^{n+1} \cdot 2^n}. \][/tex]

4. Write the Combined General Term:
Bring [tex]\( (-1)^{n+1} \)[/tex] to the numerator:
[tex]\[ a_n = \frac{9^n}{n \cdot 2^n} \cdot \frac{1}{(-1)^{n+1}} = \frac{9^n}{n \cdot 2^n} \cdot (-1)^{-(n+1)}. \][/tex]

5. Simplify the Exponent:
We know that [tex]\( (-1)^{-(n+1)} = (-1)^{-n-1} \)[/tex], so:
[tex]\[ a_n = (-1)^{-n-1} \cdot \frac{9^n}{n \cdot 2^n}. \][/tex]

6. Combine the Powers of the Numerator and Denominator:
Combine the powers of 9 / 2:
[tex]\[ a_n = \left(\frac{9}{2}\right)^n \cdot (-1)^{-n-1} \cdot \frac{1}{n}. \][/tex]

7. Express the General Term in a Simplified Form:
The simplified general term is:
[tex]\[ a_n = \frac{9^n}{n \cdot (-2)^{n+1}}. \][/tex]

Now, we can write the series:

[tex]\[ \sum_{n=1}^{\infty} \frac{9^n}{n (-2)^{n+1}} = \sum_{n=1}^{\infty} \frac{(9 / 2)^n}{n} \cdot (-1)^{-(n+1)}. \][/tex]

Final Summation Representation:
The sum of the given series can be expressed as:

[tex]\[ \boxed{\sum_{n=1}^{\infty} \frac{9^n}{n(-2)^{n+1}} = \sum_{n=1}^{\infty} \frac{(9 / 2)^n}{n} \cdot (-1)^{-(n+1)}}. \][/tex]

This is the most simplified form of the given series representation.